The effect of deposition time on the properties of titanium dioxide thin film prepared using CVD - Lias, Jais; Mohd Fauzi, Muhammad Harith Fadhilah; Sahdan, Mohd Zainizan; Nayan, Nafarizal (2020)
This research aimed to investigate effect of deposition time on the structural, morphological properties and optical properties of the titanium dioxide (TiO2) thin film prepared using Chemical Vapour Deposition (CVD). This research involved two processes which are samples preparation process and characterisation process to fulfil the aim. The samples preparation process was done by synthesising TiO2 on indium thin oxide (ITO) substrates heated at 60 ̊C substrate temperature. Titanium butoxide used as the precursor for this chemical reaction was volatilised at 210 ̊C. Oxygen gas was flown at 1 litre per minute as the carrier gas. In order to study the effect of deposition time, the synthesise of the thin films were varied to 15, 30, 45 and 60 minutes. After synthesising process, the samples underwent thermal treatment via annealing process for 1 hour at 500 ̊C. For the characterisation process, Raman Spectroscopy technique was employed to investigate the structural properties of the samples. Apart from that, Field Emission Microscopy (FEM) technique, which was performed via FE-SEM, was employed to investigate the morphologies of the samples. Other than that, UV-Vis spectrometry was employed to analyse the optical properties of the samples. Analysis of data from Raman spectroscopy displayed four Raman Shifts for each sample which confirms that the samples exhibit TiO2 of anatase phases. Whereas, images from FE-SEM displayed reduction of nanoparticle clusters on the samples as the rate of deposition time increases. Meanwhile, UV-Vis analysis displayed transmittance of the samples ranging between 50% to 80% transmittance and each sample exhibits the same optical band gap at 3.25 eV.